Lipid Binding Regulates Synaptic Targeting of PICK1, AMPA Receptor Trafficking, and Synaptic Plasticity - Wenying Jin; Woo‐Ping Ge; Junyu Xu; Mian Cao; Lisheng Peng; Wing‐Ho Yung; Dezhi Liao; Shumin Duan; Mingjie Zhang; Jun Xia (2006)
The targeting and surface expression of membrane proteins are critical to their functions. In neurons, synaptic targeting and surface expression of AMPA-type glutamate receptors were found to be critical for synaptic plasticity such as long-term potentiation and long-term depression (LTD). PICK1 (protein interacting with C kinase 1) is a cytosolic protein that interacts with many membrane proteins, including AMPA receptors via its PDZ (postsynaptic density-95/Discs large/zona occludens-1) domain. Its interactions with membrane proteins regulate their subcellular targeting and surface expression. However, the mechanism by which PICK1 regulates protein trafficking has not been fully elucidated. Here, we show that PICK1 directly binds to lipids, mainly phosphoinositides, via its BAR (Bin/amphiphysin/Rvs) domain. Lipid binding of the PICK1 BAR domain is positively regulated by its PDZ domain and negatively regulated by its C-terminal acidic domain. Mutation of critical residues of the PICK1 BAR domain eliminates its lipid-binding capability. Lipid binding of PICK1 controls the subcellular localization of the protein, because BAR domain mutant of PICK1 has diminished synaptic targeting compared with wild-type PICK1. In addition, the BAR domain mutant of PICK1 does not cluster AMPA receptors. Moreover, wild-type PICK1 enhances synaptic targeting of AMPA receptors, whereas the BAR domain mutant of PICK1 fails to do so. The BAR domain mutant of PICK1 loses its ability to regulate surface expression of the AMPA receptors and impairs expression of LTD in hippocampal neurons. Together, our findings indicate that the lipid binding of the PICK1 BAR domain is important for its synaptic targeting, AMPA receptor trafficking, and synaptic plasticity.